2006
DOI: 10.1111/j.1398-9995.2006.01195.x
|View full text |Cite
|
Sign up to set email alerts
|

The α‐chain of high‐affinity receptor for IgE (FcɛRIα) gene polymorphisms and serum IgE levels

Abstract: Our findings of genotype-related differences in IgE levels in allergic patients suggest an impact of -344 C>T but not -95 T>C gene polymorphism of FcepsilonRIalpha on total levels of IgE. The genetic variability in FcepsilonRIalpha at the -344 nucleotide of its regulatory sequence, though not related to atopy, predicts higher levels of the immunoglobulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
70
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 15 publications
10
70
4
Order By: Relevance
“…The necessity of the ␣-chain in IgE-mediated allergic reactions was definitively proved by the abolishment of anaphylaxis in ␣-chain-deficient mice (1). Recently, several groups including us reported studies regarding the association of Ϫ315 and Ϫ66 SNPs in the ␣-chain promoter with allergic diseases (2)(3)(4)(5). In the present study, we analyzed the role of these SNPs in the function of the ␣-chain promoter and found that the Ϫ315C and Ϫ315T sequences are recognized by two different transcription factors, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…The necessity of the ␣-chain in IgE-mediated allergic reactions was definitively proved by the abolishment of anaphylaxis in ␣-chain-deficient mice (1). Recently, several groups including us reported studies regarding the association of Ϫ315 and Ϫ66 SNPs in the ␣-chain promoter with allergic diseases (2)(3)(4)(5). In the present study, we analyzed the role of these SNPs in the function of the ␣-chain promoter and found that the Ϫ315C and Ϫ315T sequences are recognized by two different transcription factors, as summarized in Fig.…”
Section: Discussionmentioning
confidence: 87%
“…Recently, two independent groups reported that an SNP at Ϫ315 (Ϫ344) but not Ϫ66 (Ϫ95) is associated with IgE levels in allergic patients with asthma or urticaria (4), or IgE levels in aspirin-intolerant chronic urticaria (5). Interestingly, these two SNPs at Ϫ315 and Ϫ66 were not judged to be in LD in one report (5), whereas they were concluded to be in complete LD in another one (4,17). The latter study showed allele frequency including both SNPs; in brief, Ϫ315T/Ϫ66T is the most common, the two haplotype variants Ϫ315C/Ϫ66T and Ϫ315C/Ϫ66C occur with similar frequency, and Ϫ315T/Ϫ66C is absent in Polish population (4,17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations